Early intervention of baicalin suppresses obesity-induced adipose tissue fibrotic remodeling through Interfering NF-κB/HIF-1ɑ/GRK2 Signaling Pathway - Ying Zeng; Wenting Li; Tingting Ma; Honglei Zhang; Jiaxing Xu; Kang Liu (Phytomedicine Plus)
Obesity-induced adipose tissue (AT) fibrosis is difficult to reverse, indicating the importance of early intervention. G protein-coupled receptor kinase 2 (GRK2) is a potential regulator of energy metabolism. Baicalin can improve insulin sensitivity and metabolic homeostasis. However, their impacts on AT fibrosis have not been deciphered. This study aims to uncover the influence of early baicalin intervention on GRK2-related AT fibrotic remodeling under lipid overload. Mice were fed a high-fat diet (HFD) for 8 weeks and received baicalin or metformin during the whole period. 3T3-L1 adipocytes were pre-treated with baicalin, metformin, or pharmacological inhibitors before exposure to palmitic acid (PA) or hypoxia for 20 h. Sometimes, Cells were transfected with siRNA or plasmid DNA specific for GRK2. Results showed that increased GRK2 in AT was observed early after HFD feeding. GRK2 silencing in adipocytes attenuated the profibrotic activation and improved insulin sensitivity and adipokine secretion, but GRK2 overexpression had the opposite effect. Baicalin treatment resulted in the downregulation of GRK2 in 3T3-L1 adipocytes and epididymal AT from the early stage after lipid overload, prevented the profibrotic response, and ameliorated systemic and local insulin resistance. In addition, the negative regulation of GRK2 by baicalin was associated with reduced NF-κB phosphorylation and HIF-1ɑ abundance. Collectively, baicalin prevents HFD-induced AT fibrosis and ameliorates insulin resistance by interfering NF-κB/HIF-1ɑ/GRK2 signaling pathway. This finding provides a better insight into the regulatory effect of baicalin on AT homeostasis and reinforces its promising role in managing obesity-related diseases.